Breeding strategy and contract farming model to promote Boer Cross population continuity: A case study at Sadhana Arif Nusa Company Lombok Island West Nusa Tenggara Province, Indonesia) - Lalu Ahmad Zaenuri; I Wayan Lanus Sumadiasa; Lalu Wira Pribadi (Livestock and Animal Research, 2023)
Objective: This study aims to analyze population development strategies and contract farming models with East Lombok regency West Nusa Tenggara province farmers. This research was focused on SAN-C which is very concerned with the development of Boer goats and employing the people of East Lombok.Methods: The study employed action research. Boer cross-goats data was obtained from the log book of SAN-C. Supporting data were obtained from in-depth interviews and FGDs with representatives of farmers, livestock traders, representatives of the East Lombok district government, and management representatives of SAN-C.Results: This study found that the previous contract farming model with the credit system was changed to a profit-sharing system based on the weight of the goat. That is the difference in the final weight minus the initial weight multiplied by the price per kilogram divided by two. One part is for partners, and the other part is for SAN-C. Thus, the income for farmers is close to the minimum standard wage for the district of East Lombok.Conclusion: By applying a new breeding strategy and contract farming models, the population of Boer cross increased sustainably. Similarly, the income of farmers will also increase. It is recommended that the new contract farming model can be applied to other farmers all over WNT. It was also recommended that both SAN-C and must make a selection, especially for F2 and F3 with the most superior phenotypes as stock breeders. Finally, excess feed production in the rainy season should be stored in the form of hay or silage to overcome the shortage of feed in the dry season.